Assessing the questionnaires on perceived oral healthcare need: A systematic review - Zahra Yaghoubi (Journal of Oral Health and Oral Epidemiology, 2017)
BACKGROUND AND AIM: Perception of the need for oral healthcare plays a key role in creating motivation and demand for utilization of oral healthcare services. Furthermore, while the lack of resources, people with perceived needs to oral healthcare, due to the higher profit potential of services, will be on higher priority for services. The aim of this study was to undertake a systematic review of the existing literature about questionnaires used for assessing the perceived oral healthcare needs.